Experimental murine chromoblastomycosis obtained from Fonsecaea pedrosoi isolate cultured for a long periodt - Machado,AP (2009)
The present study aimed to describe F. pedrosoi propagules capable of causing chronic murine disease. Several changes in F. pedrosoi hyphae were identified in fungal cells cultured for a long period. Optical microscopy found many rounded cells with double-rigid melanin-rich walls. Terminal and intercalary chlamydoconidia were also frequently observed. Analyses of images from transmission electron microscopy (TEM) revealed several cells with walls composed of at least three layers and an outer layer enriched with melanin. Two groups of twenty BALB/c mice were subcutaneously infected in their footpads with F. pedrosoi cells at an inoculum concentration of approximately 1 x 10(4) cells/mL. In one group, long-term cultured F. pedrosoi cells were inoculated in one footpad, whereas in the other group, both footpads were infected. Active lesions were observed up to seven months post-infection, particularly in mice inoculated at two sites. After this period, animals were killed. Histological sections revealed characteristics bearing a strong resemblance to the human form of the disease such as tissue hyperplasia, granulomas with microabscesses and sclerotic cells. Based on this study, we identified fungal cells from old cultures capable of provoking chronic chromoblastomycosis under experimental conditions, especially when more than one site is infected.